SIKAP MASYARAKAT TENTANG PEMANFAATAN JAMBAN KELUARGA DI WILAYAH KERJA PUSKESMAS PEMBANTU NELAYAN, KELURAHAN NELAYAN INDAH, KECAMATAN MEDAN LABUHAN - Dewi Agustina; Anastasya Khairiah; Annisa Ramadhani; Putri Aulia Azmi (Universitas Islam Negeri Sumatera Utara, 2022)
Abstract A latrine is a building that is used to be called a place to dispose of and collect human waste or najis, usually a latrine/WC. So that the results will be stored in a certain place and not be the cause or spread of disease and pollute the residential environment (Depkes RI, 2003). This research was conducted to determine the description of community behavior regarding the use of family latrines in the Nelayan Indah Village, Medan Labuhan District. Data collection was done by interview and observation. The research instrument used an observation sheet in the form of a questionnaire. The results of the research on family latrine ownership of 120 respondents showed that 92.5% had a latrine and 7.5% did not. the results of the research on the use of family latrines from 120 respondents showed that 90.8% used latrines and 9.2% did not use latrines. The results of this study indicate that the knowledge, attitudes and actions of the community in the fishing village of Indah in the ownership and use of latrines are quite good. The community already knows the importance of using good healthy family latrines and completely avoiding diseases caused by dirt or feces